Archiving a TEI Project FAIRly - Andrew Creamer; Gaia Lembi; Elli Mylonas; Michael Satlow (Journal of the Text Encoding Initiative)
The Inscriptions of Israel/Palestine project is an online corpus of over four thousand inscriptions from Israel and Palestine, written in Hebrew, Greek, Latin, and Aramaic, dating roughly from the Persian Period to the Arab Conquest. The source files with inscription text and metadata are encoded using EpiDoc, a TEI customization widely used by epigraphers. As the project prepared to deposit its XML files in an institutional repository, it transformed them into a locally developed robust archival format. This paper evaluates these decisions against the FAIR metrics, using IIP as a test case. This allows us to suggest improvements for our own archival encoding as well as to see where EpiDoc and TEI enhance FAIRness and where they could provide more support. Finally, we suggest some ways to use FAIR metrics that are more amenable to TEI documents and corpora.